Cannabinoids in Health and Disease - Meccariello, Rosaria; Chianese, Rosanna (IntechOpen, 2016)
This book provides a comprehensive overview of current knowledge of cannabinoid activity in human physiology and points out the importance of endocannabinoid system for the maintenance of human health and treatment of diseases. Each chapter has been organized with the aim to cover basic concepts in the modulation of endocannabinoid system in both physiological and pathological conditions, thanks to the integration of data from experimental animal models and clinical observations. A special focus has been put on the medical use of cannabinoids and on the targeting of endocannabinoid system as new therapeutic strategy for the prevention and treatment of human diseases. Taken together, this book targets a wide audience of basic and clinical scientists, teachers and students interested in gaining a better understanding in the field of cannabinoids.